Assessment of Urological Knowledge and Practice Among Emergency and Primary Health Care Physicians - Badr Alharbi; Emad Alwashmi; Faisal Awadh Al-Harbi; Adel H. Alharbi; Abdulaziz Alhuraisi; Khaled Almansour; Watban Alwatban; Abdulrahman Saleh Alqazlan; Adil Khalaf Altwairgi (International Journal of Biomedicine)
Background: Emergency and primary health care (PHC) are critical settings for addressing urological health problems and related emerging complaints. Therefore, physicians in these fields must possess the knowledge, skills, and competencies to diagnose and manage common urologic presentations accurately. This study aimed to evaluate the general level of knowledge about common urological problems among PHC and emergency room physicians in Qassim province, Saudi Arabia. Methods and Results: A cross-sectional questionnaire-based study included 82 PHC and emergency room physicians. The study was mainly a descriptive study utilizing non-probability convenience sampling of all participants who completed online or hardcopy surveys. As for the urological knowledge, it was found that 40.2% of the participants knew correctly that prostate-specific antigen (PSA) screening should be performed on a 60-year-old man who presents with urinary retention. In addition, 40.2% knew that patients should be referred for further urological evaluation of hematuria if they have a single episode of gross hematuria, a finding of microhematuria on 3 successive urine analyses, or when persistent microhematuria after treatment with antibiotics is present. Only 23.2% knew that when inserting a Foley catheter in a man, it is appropriate to inflate the balloon after the catheter has been inserted at its full length or when urine return is noted. More than half (58.5%) knew that patients should be referred to a urologist if they have a nodular prostate. Only 24.4% knew that the best test to evaluate for the presence of a kidney stone is a CT abdomen/pelvis, and 63.4% correctly defined microscopic hematuria. As for the participants’ urological skills, 70.7% agreed that they were proficient in performing a digital rectal examination and 76.9% said they performed male genitourinary examinations; 87.8% agreed that they are proficient in taking sexual history, 23.2% performed digital rectal examination >20 times, and 31.7% performed male genitourinary examination >20 times; 79.3% agreed they were proficient in performing male urinary catheterization, while 79.3% were proficient in performing female urinary catheterization. Only 24.4% were proficient in the insertion of a suprapubic catheter. As for the practice frequency, 37.8% performed male urinary catheterization more than 20 times, while only 12.2% performed it for females at the same frequency. Conclusion: The general knowledge of emergency and PHC physicians in the Qassim region appears insufficient. The study identified significant gaps in urological knowledge among these physicians, highlighting the need for adequate training programs to bridge these gaps.